2018
DOI: 10.1161/jaha.118.009777
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Remodeling of Mitral Valve Leaflets from Unphysiologic Leaflet Mechanics after Undersized Mitral Annuloplasty to Repair Ischemic Mitral Regurgitation

Abstract: Background Undersized ring annuloplasty is a commonly used surgical repair for ischemic mitral regurgitation, in which annular downsizing corrects regurgitation, but alters valve geometry and elevates tissue stresses. In this study, we investigated if unphysiological leaflet kinematics after annuloplasty might cause pathogenic biological remodeling of the mitral valve leaflets, and if preserving physiologic leaflet kinematics with a better technique can moderate such adverse remodeling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…In a swine experimental model of moderate IMR, pathogenic biological changes in the MV leaflets were demonstrated within a short period of 3 months. Collagen levels were elevated in these stressed leaflets and the profibrotic changes in the valve paralleled increase in TGF‐β 47 . Surgical repair with restrictive mitral annuloplasty alone frequently do not restore physiological leaflet configuration and, if mechanical strains remains elevated, pathogenic changes in valve leaflets can be induced.…”
Section: Resultsmentioning
confidence: 99%
“…In a swine experimental model of moderate IMR, pathogenic biological changes in the MV leaflets were demonstrated within a short period of 3 months. Collagen levels were elevated in these stressed leaflets and the profibrotic changes in the valve paralleled increase in TGF‐β 47 . Surgical repair with restrictive mitral annuloplasty alone frequently do not restore physiological leaflet configuration and, if mechanical strains remains elevated, pathogenic changes in valve leaflets can be induced.…”
Section: Resultsmentioning
confidence: 99%
“…We hope that we have taken a first step toward similar studies that may support pharmacological support of TR surgery and/or intervention. Interestingly, recent work has demonstrated that not only disease, but also surgical repair may initiate mitral valve tissue (mal)adaptation (54). It is possible that the tricuspid valve, similarly, may (mal)adapt to repair.…”
Section: Discussionmentioning
confidence: 99%
“…27 Altered mechanical loads following undersized ring annuloplasty and/or papillary muscle approximation also show differences in several genes related to ECM remodeling. 28 This feedback interaction between VICs and their micro-mechanical environment and the way this scales to the levels of the tissue and organ (valve and ventricle) warrants further investigation, especially in the context of IMR.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent reports have continued to shed light on the MV remodeling processes post-MI, either unaltered 23,29,30 or in the context of various interventions 25,28,31 , fundamental questions regarding MV remodeling in IMR remain. In particular, detailed analyses of the functional physiological behaviors of the post-MI MV necessary for informing advanced computational simulations of patient-specific surgical procedures remain lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation